2022
DOI: 10.3389/fpsyt.2022.897157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-Acceptance and Intention to Stay at Work Among Clinical Nurses in China: A Cross-Sectional Online Survey

Abstract: BackgroundDuring the pandemic and with the growing shortage of nurses, the problem of how to retain existing nurses was of paramount importance. However, there is limited evidence on the relationship between nurses' self-acceptance and intention to stay.ObjectivesThis study aimed to investigate the factors influencing nurses' intention to stay at work, and explore the relationship between self-acceptance and their intention to stay.MethodsConvenience sampling was conducted to select nurses who worked in a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…This also shows that the organisation is able to promote well-being and enhance the employees' strengths within their work. Furthermore, a study among clinical nurse in China indicated that self-acceptance is one of the factors that influence employee's intention to stay at work (Kong, Qin, Zhou, Ding, & Qu, 2022). This may further propose that high levels of self-acceptance among the respondents in the current study enhances their determination to continue working at the company.…”
Section: Employee Psychological Well-beingmentioning
confidence: 62%
“…This also shows that the organisation is able to promote well-being and enhance the employees' strengths within their work. Furthermore, a study among clinical nurse in China indicated that self-acceptance is one of the factors that influence employee's intention to stay at work (Kong, Qin, Zhou, Ding, & Qu, 2022). This may further propose that high levels of self-acceptance among the respondents in the current study enhances their determination to continue working at the company.…”
Section: Employee Psychological Well-beingmentioning
confidence: 62%
“…Iverson and Pullman [9] pointed out that employees with family responsibilities are more inclined to stay. Bao et al [10] found that employees with self-acceptance values are more likely to choose to stay [11]. Cinar et al [12] showed that employees' personal work relationship remodeling positively impacts intention to stay, with workplace friendships playing a partial mediating role.…”
Section: Individual Factorsmentioning
confidence: 99%